2022
DOI: 10.2196/preprints.43570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Trend of COVID-19 Vaccination Rate and Its associated factors: a multicenter household survey (Preprint)

Abstract: BACKGROUND Vaccination against COVID-19 has saved tens of thousands of lives worldwide since its introduction. However, with time elapsing, improving the vaccination coverage in China may be confronted with a number of obstacles. OBJECTIVE In this nationwide study, we aimed to evaluate the COVID-19 vaccination rate and its potential influencing factors in the Chinese population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This stance is one of the biggest threats to global health today. The prevalence of acceptance of vaccination in developed countries such as the USA, France and Italy is less than 60%, exhibiting lower values in places such as Russia, the Middle East and African countries [6]. Several studies have shown that this hesitation becomes more important when it comes to vaccinating children and adolescents [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This stance is one of the biggest threats to global health today. The prevalence of acceptance of vaccination in developed countries such as the USA, France and Italy is less than 60%, exhibiting lower values in places such as Russia, the Middle East and African countries [6]. Several studies have shown that this hesitation becomes more important when it comes to vaccinating children and adolescents [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%